2021
DOI: 10.3390/ijerph18063324
|View full text |Cite
|
Sign up to set email alerts
|

Daily Life Changes and Life Satisfaction among Korean School-Aged Children in the COVID-19 Pandemic

Abstract: The recent COVID-19 pandemic has been disrupting the daily lives of people across the world, causing a major concern for psychological well-being in children. This study aimed to examine (1) how life satisfaction and its potential predictors have been affected by the pandemic among school-aged children in Korea, and (2) which factors would predict their life satisfaction during the pandemic. We surveyed 166 fourth-graders in the Seoul metropolitan area to assess their psychological well-being and potentially r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 75 publications
(109 reference statements)
5
48
0
1
Order By: Relevance
“…Life satisfaction during COVID-19erelated lockdown restrictions decreased (stringency index: 78.80), which is in line with two longitudinal studies reporting that life satisfaction of Australian adolescents decreased during the pandemic compared with before (stringency index: 65.74e69.44) [19,20]. It should be noted that the findings could be specific for adolescents, as a decline in life satisfaction was not observed in younger children (aged 8e10 years, stringency index: 50.46e65.74) living in South Korea nor in Chinese youth (aged 6e17 years) (stringency index: 79.17e81.02) [40,41]. In contrast to life satisfaction, there was no change in internalizing symptoms observed in our sample.…”
Section: Results In the Context Of Previous Literaturementioning
confidence: 84%
“…Life satisfaction during COVID-19erelated lockdown restrictions decreased (stringency index: 78.80), which is in line with two longitudinal studies reporting that life satisfaction of Australian adolescents decreased during the pandemic compared with before (stringency index: 65.74e69.44) [19,20]. It should be noted that the findings could be specific for adolescents, as a decline in life satisfaction was not observed in younger children (aged 8e10 years, stringency index: 50.46e65.74) living in South Korea nor in Chinese youth (aged 6e17 years) (stringency index: 79.17e81.02) [40,41]. In contrast to life satisfaction, there was no change in internalizing symptoms observed in our sample.…”
Section: Results In the Context Of Previous Literaturementioning
confidence: 84%
“…Smartphone addiction is a common but growing issue among adolescents in South Korea [9], and studies in that country and others have shown that smartphone addiction and/or problematic smartphone use have increased among adolescents and adults since the COVID-19 pandemic [1,2,11,16,17]. South Korean fourth graders were more prone to smartphone addiction before COVID-19 than during [1]. However, problematic smartphone use prevalence was higher among Chinese primary schoolchildren during a COVID-19-related lockdown than before the pandemic [2].…”
Section: Smartphone Addiction Among Adolescents Since Covid-19mentioning
confidence: 99%
“…The COVID-19 pandemic has greatly affected children's and adolescents' lives around the world. Compared to before the pandemic, children and adolescents have drastically increased their screentime, including their use of smartphones, and more children and adolescents are considered to be addicted to their smartphone or are engaging in problematic smartphone use than before the pandemic [1,2]. Moreover, children and adolescents are more depressed now than before the pandemic [3,4], and smartphone addiction and problematic smartphone use have been found to be positively associated with depression, although this data includes studies conducted before COVID-19 [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations